Turn it and turn it again: studies in the teaching and learning of classical Jewish texts - Levisohn, Jon A.; Fendrick, Susan P. (Jewish Identities in Post-Modern Society, 2013)
Frontmatter -- Contents -- Acknowledgements -- Foreword / Feiman-Nemser, Sharon -- 1. Cultivating Curiosity about the Teaching of Classical Jewish Texts / Levisohn, Jon A. / Fendrick, Susan P. -- PART 1: Focus on Subject Matter -- 2. A Map of Orientations to the Teaching of Bible / Holtz, Barry W. -- 3. What Are the Orientations to the Teaching of Rabbinic Literature? / Levisohn, Jon A. -- 4. Teaching Talmudic Hermeneutics Using a Semiotic Model of Law / Reifman, Daniel -- 5. Neusner, Brisk, and the Stam: Significant Methodologies for Meaningful Talmud Teaching and Study / Chernick, Michael -- PART 2: Focus on Teaching and Teachers -- 6. The Pedagogy of Slowing Down: Teaching Talmud in a Summer Kollel / Kanarek, Jane -- 7. Serendipity and Pedagogy: Presenting the Weekly Parashah through Rabbinic Eyes / Perkins, Carl M. -- 8. Introducing the Bible: The Comparative Orientation in Practice / Levisohn, Jon A. -- PART 3: Focus on Learning and Learners -- 9. Teaching Ancient Jewish History: An Experiment in Engaged Learning / Satlow, Michael L. -- 10. "A Judaism That Does Not Hide": Curricular Warrants for the Teaching of the Documentary Hypothesis in Community Jewish High Schools / Tanchel, Susan E. -- 11. Developing Student Awareness of the Talmud as an Edited Document: A Pedagogy for the Pluralistic Jewish Day School / Spitzer, Jeffrey -- 12. A Theory of Havruta Learning / Kent, Orit -- PART 4: Focus on Context -- 13. "Torah Talk": Teaching Parashat Ha-shavua to Young Children / Horowitz, Shira -- 14. Using the Contextual Orientation to Facilitate the Study of Bible with Generation X / Cousens, Beth / Fendrick, Susan P. / Morrison, Jeremy S. -- 15. Academic Study of the Talmud as a Spiritual Endeavor in Rabbinic Training: Delights and Dangers / Steinberg, Jonah Chanan -- 16. Teaching Rabbinics as an Ethical Endeavor and Teaching Ethics as a Rabbinic Endeavor / Lev, Sarra -- List of Contributors -- Index of Biblical and Rabbinic Sources -- General Index